1999
DOI: 10.1021/jp9838893
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopy of H2S and SH in Rare-Gas Matrixes

Abstract: Infrared (IR) spectra of hydrogen sulfide (H2S), some of its complexes, and their photolysis products are studied in rare-gas matrixes (Ar, Kr and Xe) at 7.5 K. In all of these matrixes, H2S is found to undergo hindered rotation. The vibration−rotation structures of monomeric H2S are observed at 2651−2615, 2640−2600, and 2625−2580 cm-1 in Ar, Kr, and Xe matrixes, respectively. Furthermore, the H2S dimer and the H2S···H2O complex are observed in various matrixes. Upon UV-induced decomposition of H2S, IR absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 56 publications
4
42
0
Order By: Relevance
“…The bands at 2578 cm -1 is the characteristic frequency of ν s (SH) of surface HS. 20,21 The peak at 3755 cm -1 for surface hydroxyl 22 decreased in intensity as a function of time. The bands at 1659 and 1409 cm -1 were assigned to ν as (OCO) and ν s (OCO) of surface HCO 3 -species, which were accompanied by ν(OH) and δ(OH) at 3618 and 1225 cm -1 , respectively.…”
Section: Heterogeneous Reaction Of Ocs On Mgo In Closedmentioning
confidence: 98%
“…The bands at 2578 cm -1 is the characteristic frequency of ν s (SH) of surface HS. 20,21 The peak at 3755 cm -1 for surface hydroxyl 22 decreased in intensity as a function of time. The bands at 1659 and 1409 cm -1 were assigned to ν as (OCO) and ν s (OCO) of surface HCO 3 -species, which were accompanied by ν(OH) and δ(OH) at 3618 and 1225 cm -1 , respectively.…”
Section: Heterogeneous Reaction Of Ocs On Mgo In Closedmentioning
confidence: 98%
“…We used SO 2 ͑Ͼ99.9%, Fluka͒, Ar ͑Ͼ99.9999%, AGA͒, and H 2 S 2 synthesized by cracking sulfanes (H 2 S n ) as described elsewhere. 24 The gas mixture was deposited onto a CsI substrate in a closed cycle helium cryostat ͑DE-202A, APD͒, providing temperatures down to 7.5 K. The temperature was measured with a silicon diode ͑accuracy 0.5 K͒, and a resistive heater provided higher temperatures.…”
Section: A Experimental Detailsmentioning
confidence: 99%
“…24,29 In the 193-nm photolysis, this absorption band disappears typically after some hundreds of pulses. S 2 molecules were found to be the major product among sulfur-containing species in 193-nm photolysis of H 2 S 2 .…”
Section: B H 2 S 2 /Ar Matricesmentioning
confidence: 99%
“…After two hours of irradiation, a band appears at 2507 cm −1 . One possible assignment of this band is the H 2 S 2 dimer or H 2 S 2 -H 2 S complex, based on previous assignments by Isoniemi et al (1999). The S-H stretching mode of H 2 S 2 is in the same position as the H 2 S band (in the mixture H 2 S-H 2 O) at 2550 cm −1 , precluding direct detection of H 2 S 2 .…”
mentioning
confidence: 95%
“…H 2 S 2 formed early in the irradiation is likely dissociated by the irradiation and may react to form larger molecules. Isoniemi et al (1999) studied UV photolysis of H 2 S 2 ice in an Ar matrix and concluded that this photochemistry leads to the formation of the HS 2 radical and S 2 . Dissociation of H 2 S 2 presumably contributes to the production of S 2 detected by TPD.…”
mentioning
confidence: 99%